In vitro and in vivo study of ABT-869 in treatment acute myeloid leukemia (AML) alone or in combination with chemotherapy or HDAC inhibitors: insight into molecular mechanism and biologic characterization - ZHOU JIANBIAO (2010)
Ph.D